Low-cost biodiesel production using waste oil and catalyst. Issue 2 (February 2021) - Talavari, Raheleh; Hosseini, Shokoufe; Moradi, GR
With the production of renewable biofuels, concerns about the end of fossil fuels have been partially eliminated. On the other hand, the utilization of low-cost and waste materials to provide the raw essential substances to manufacture these fuels is of paramount importance. Biodiesel is one of these fuels and the required raw materials for the reaction are oil (triglycerides), alcohol and catalyst. In this work, travertine stone powder (as waste in the manufacture of building materials) was used as a catalyst and waste frying oil as a source of triglyceride for biodiesel production. Using thermogravimetric and X-ray diffraction analysis, optimum temperature for catalyst calcination was selected at 900°C. Furthermore, X-ray fluorescence, Fourier transform infrared spectroscopy, Brunauer–Emmett–Teller, transmission electron microscopy and scanning electron microscopy analyses were performed. Using the design of experiments Response Surface Methodology, the optimum reaction conditions for biodiesel production yield of 97.74% were: reaction temperature 59.52°C (~60°C), time 3.8 h (228 min), catalyst concentration 1.36 wt.% and the methanol to oil molar ratio of 11:6. After reusing four times, the catalyst efficiency was reduced a little, and the biodiesel yield was 89.84%, indicating high strength and stability of the catalyst.